Self-Development Of Future Primary School Teachers - Karimova Kunduz Ruzibayevna (Frontline Social Sciences and History Journal, 2026)
This article discusses the teaching profession and the self-development of future teachers, emphasizing the decisive role of the primary school teacher’s personality in pupils’ intellectual, moral, and social development. It also outlines pedagogical conditions for forming a need for self-development in future teachers. The concept of self-development is viewed as a conscious and goal-oriented activity of the individual. Pedagogy and psychology explain that this process is based on internal needs and highlight the importance of its implementation in professional, methodological, and personal directions.